Using the Experience of the International Consortium to Shape the University Strategy for E-Learning - Bekić, Zoran (Array, 2007)
The paper is based on the authors' experience in coordinating EU Tempus project EQIBELT: Education Quality Improvement by E-Learning Technology. The paper presents the conclusions of the EQIBELT policy workshop on creating e-learning vision and strategy. Most of the conclusions are based on experience and best practices of eight European universities - members of the EQIBELT consortium. The paper also deals with the basic elements of the E-Learning strategy of University of Zagreb, which was shaped in the framework of the EQIBELT project. Paper points out the value of experience accumulated within the consortium, but also emphasizes that it is highly important to find an appropriate particular way of introducing and using e-learning at each university in particular circumstances. It is also very important to precisely define concrete strategic goals for implementation of e-learning at particular university and to provide and settle strict implementation plan for the e-learning strategy.